New small-bodied ornithopods (Dinosauria, Neornithischia) from the Early Cretaceous Wonthaggi Formation (Strzelecki Group) of the Australian-Antarctic rift system, with revision of Qantassaurus intrepidus Rich and Vickers-Rich, 1999. (11th March 2019) - Herne, Matthew C.; Nair, Jay P.; Evans, Alistair R.; Tait, Alan M.
Abstract: The Flat Rocks locality in the Wonthaggi Formation (Strzelecki Group) of the Gippsland Basin, southeastern Australia, hosts fossils of a late Barremian vertebrate fauna that inhabited the ancient rift between Australia and Antarctica. Known from its dentary, Qantassaurus intrepidus Rich and Vickers-Rich, 1999 has been the only dinosaur named from this locality. However, the plethora of vertebrate fossils collected from Flat Rocks suggests that further dinosaurs await discovery. From this locality, we name a new small-bodied ornithopod, Galleonosaurus dorisae n. gen. n. sp. from craniodental remains. Five ornithopodan genera are now named from Victoria. Galleonosaurus dorisae n. gen. n. sp. is known from five maxillae, from which the first description of jaw growth in an Australian dinosaur is provided. The holotype of Galleonosaurus dorisae n. gen. n. sp. is the most complete dinosaur maxilla known from Victoria. Micro-CT imagery of the holotype reveals the complex internal anatomy of the neurovascular tract and antorbital fossa. We confirm that Q. intrepidus is uniquely characterized by a deep foreshortened dentary. Two dentaries originally referred to Q. intrepidus are reassigned to Q. ? intrepidus and a further maxilla is referred to cf. Atlascopcosaurus loadsi Rich and Rich, 1989. A further ornithopod dentary morphotype is identified, more elongate than those of Q. intrepidus and Q. ? intrepidus and with three more tooth positions. This dentary might pertain to Galleonosaurus dorisae n. gen. n. sp. Phylogenetic analysis recovered Cretaceous Victorian and Argentinian nonstyracosternan ornithopods within the exclusively Gondwanan clade Elasmaria. However, the large-bodied taxon Muttaburrasaurus langdoni Bartholomai and Molnar, 1981 is hypothesised as a basal iguanodontian with closer affinities to dryomorphans than to rhabdodontids. UUID: http://zoobank.org/4af87bb4-b687-42f3-9622-aa806a6b4116